2021
DOI: 10.1002/eji.202049004
|View full text |Cite
|
Sign up to set email alerts
|

Driving T cells to human atherosclerotic plaques: CCL3/CCR5 and CX3CL1/CX3CR1 migration axes

Abstract: T‐cell accumulation in atherosclerotic plaques contributes to plaque destabilization. We found that several chemokine receptors are differentially expressed on peripheral blood compared to plaque‐resident T cells and corresponding ligands are upregulated in plaques. These data indicate that T‐cell migration into human atherosclerotic plaques may predominantly occur via CCR5‐CCL3 and CX3CR1‐CX3CL1 interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
4
13
0
Order By: Relevance
“…We found that genes associated with aging can make a signi cant difference in macrophage subtypes in the progression of atherosclerosis by immune in ltration analysis. CCL3, as a cytokine, is also one of the hub genes in this study, which may play an important role in monocyte recruitment to form plaques 27 . It was found that the knockdown of CCL3 in mice delayed the progression of nonalcoholic hepatitis 28 .…”
Section: Discussionmentioning
confidence: 87%
“…We found that genes associated with aging can make a signi cant difference in macrophage subtypes in the progression of atherosclerosis by immune in ltration analysis. CCL3, as a cytokine, is also one of the hub genes in this study, which may play an important role in monocyte recruitment to form plaques 27 . It was found that the knockdown of CCL3 in mice delayed the progression of nonalcoholic hepatitis 28 .…”
Section: Discussionmentioning
confidence: 87%
“…The progression of plaques is also related to lymphocyte activation, including B2 and T lymphocytes [ 98 ]. Atherosclerotic plaque destabilization, related to activation of neutrophils [ 99 , 100 ], monocytes [ 101 ] and lymphocytes [ 102 , 103 ] has also been postulated.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al ( 31 ) considered that direct inhibition of CCL4 stabilized atheroma and reduced endothelial and macrophage activation. Komissarov et al ( 33 ) reported that T-cell migration into human atherosclerotic plaques may predominantly occur via C-C motif chemokine receptor 5-CCL3 and C-X3-C motif chemokine receptor 1-C-X3-C motif chemokine ligand 1 interactions. Munjal and Khandia ( 34 ) suggested that the chemokines (family of small cytokines) involved in atherosclerotic plaque formation are CCL3, chemokine (C-X-C motif) ligand 4 and macrophage migration-inhibitory factor.…”
Section: Discussionmentioning
confidence: 99%